1984
DOI: 10.1136/jmg.21.4.281
|View full text |Cite
|
Sign up to set email alerts
|

Familial hidradenitis suppurativa: evidence in favour of single gene transmission.

Abstract: SUMMARY The three English families in this report have a total of 21 members (16 females and five males) suffering from chronic hidradenitis suppurativa. In family A the condition is associated with acne conglobata and there is vertical transmission of the disorder through three generations. In the others there is no associated cystic acne, but all those affected had a history of acne vulgaris with comedone formation, and the condition has been confirmed in two generations. It is likely that a male in an earli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
1
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 5 publications
2
31
1
2
Order By: Relevance
“…We had one pair of twins in our series, and 29% of the patients had a family history. There is thought to be a genetic form of the disease, with a single gene transmission (10,11). A correlation to acne would be conceivable, but the prevalence of acne in our patients was no higher than in the normal population (12).…”
Section: Discussioncontrasting
confidence: 54%
“…We had one pair of twins in our series, and 29% of the patients had a family history. There is thought to be a genetic form of the disease, with a single gene transmission (10,11). A correlation to acne would be conceivable, but the prevalence of acne in our patients was no higher than in the normal population (12).…”
Section: Discussioncontrasting
confidence: 54%
“…36 One study describing an autosomal dominant pattern of inheritance has also been reported, but the penetrance appeared variable, indicating that other nongenetic factors are involved. 26,37 A later review of the data has renewed the suspicion of a dominant pattern of inheritance in this group of patients using a better clinical definition of the cases. 38 Co-occurrence of phenotypes may support a genetic linking.…”
Section: Etiology and Pathogenic Factorsmentioning
confidence: 93%
“…26 ln a study of the ''hidden'' or unrecognized'' dermatological diseases in patients attending a dermatological clinic, a physical examination of general dermatological patients found a point prevalence of hidradenitis at a rate of 1/ 1000. 27 From interviews among healthy women (mean age 31 years), a lifetime prevalence rate of 4% was found.…”
Section: Epidemiologymentioning
confidence: 99%
“…Fitzsimmons et al studied three families with a total of 21 affected members. They reported that the pattern of transmission and the number of affected individuals were consistent with autosomal dominant inheritance [15].…”
Section: History -Epidemiology -Incidencementioning
confidence: 97%